Population Administration Service Innovation Through Kenduren Mas Program (Kendaraan Urun Rembuk Masyarakat) Pasuruan Regency - Ulfa, Chilmia Rochmawati Maria; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2021)
The purpose of this study is to describe and analyze the innovation of population administration services in Pasuruan Regency. in this study using a qualitative descriptive method with the technique of determining the informant, namely purposive sampling. Data collection techniques using observation, interviews, and documents. The data analysis uses Miles and Hubberman analysis, namely data reduction, data presentation, and drawing conclusions. This study concludes that the innovation of population administration services through the Kenduren Mas (Community Gathering Vehicle) program in Pasuruan Regency is seen in terms of relative advantages, namely the service becomes effective and efficient because it can be carried out in the village or location of the Kenduren Mas implementation and in terms of compatibility there are still people who do not know in detail about the procedures specified in this service. Meanwhile, complexity is the understanding of both implementers and recipients regarding the elaboration of easy and simple procedures for innovation in population administration services. However, in terms of trials, there are no other regions that have replicated the innovation program and it is easy to observe with the aim of measuring through community satisfaction surveys.